2004
DOI: 10.1086/423273
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus and Clostridium difficile Cause Distinct Pseudomembranous Intestinal Diseases

Abstract: We report simultaneous infections with Clostridium difficile and methicillin-resistant Staphylococcus aureus (MRSA) in a patient with discrete colonic pseudomembranes typical of C. difficile infection, as well as confluent, loosely adherent pseudomembranes in the small bowel. Identification of MRSA in the small bowel pseudomembrane by polymerase chain reaction supports S. aureus as an enteric pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Thus, S. aureus fecal testing may be applicable for patients with AAD of unknown cause and/or when S. aureus, particularly MRSA, has been isolated from another site. Froberg et al recently reported a case of simultaneous infections with C. difficile and S. aureus (MRSA) (17). The presence of discrete colonic pseudomembranes and confluent, loosely adherent ileal pseudomembranes suggested that separate pathological processes occur in these two types of AAD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, S. aureus fecal testing may be applicable for patients with AAD of unknown cause and/or when S. aureus, particularly MRSA, has been isolated from another site. Froberg et al recently reported a case of simultaneous infections with C. difficile and S. aureus (MRSA) (17). The presence of discrete colonic pseudomembranes and confluent, loosely adherent ileal pseudomembranes suggested that separate pathological processes occur in these two types of AAD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of investigators have reported that predominant growth of enterotoxin-producing strains of MRSA in the stool may in some instances be associated with development of enterocolitis or antibiotic-associated diarrhea (10,16,17,20,21,23,35,36,41). Despite these reports, MRSA has seldom been reported as a cause of enterocolitis or antibiotic-associated diarrhea in the United States (7,28,32). Recently, we reported 11 cases of antibiotic-associated diarrhea in patients whose stool specimens contained heavy growth of enterotoxin-producing strains of MRSA, with detectable amounts of staphylococcal enterotoxin in stool filtrates (1).…”
Section: Discussionmentioning
confidence: 99%
“…The basic mechanisms are quite enigmatic and the etiological processes are just beginning to be identified. For instance, Froberg et al [67] presented histo-pathological evidence for the existence of a specific S. aureus-induced pseudomembranous intestinal disease, distinct from that seen during C. difficile infection in an unusual case of simultaneous infection with C. difficile and MRSA. Whereas C. difficile induces colonic pseudomembranes, the MRSA infection induced loosely adherent pseudomembranes in the small bowel.…”
Section: Potential Role Of S Aureus In Intestinal Diseasementioning
confidence: 99%